2017
DOI: 10.1007/s00345-017-2085-6
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of direct in-bore magnetic resonance imaging (MRI)-guided biopsy and fusion-guided biopsy in patients with MRI lesions which are likely or highly likely to be clinically significant prostate cancer

Abstract: PurposeTo compare clinically significant prostate cancer (csPCa) detection rates between magnetic resonance imaging (MRI)–transrectal ultrasound (TRUS) fusion-guided prostate biopsy (FGB) and direct in-bore MRI-guided biopsy (MRGB).MethodsWe performed a comparison of csPCa detection rates between FGB and MRGB. Included patients had (1) at least one prior negative TRUS biopsy; (2) a Prostate Imaging Reporting and Data System (PI-RADS) 4 or 5 lesion and (3) a lesion size of ≥8 mm measured in at least one directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 17 publications
1
19
1
Order By: Relevance
“…No significant difference in the overall and Cs PCa detection rates was observed between the two groups; the first constituted of 104 patients that were subjected to fusion biopsy (39 and 32%, respectively, for the PCa and Cs PCa detection rate), while an in-bore biopsy was performed on the other 106 patients (37 and 29%, respectively, for the PCa and Cs PCa detection rate). This is in agreement with the study performed by Vanderink et al according to which there is no significant difference in the detection rate between the two biopsy techniques [24].…”
Section: Methods Of Mri-targeted Biopsysupporting
confidence: 93%
“…No significant difference in the overall and Cs PCa detection rates was observed between the two groups; the first constituted of 104 patients that were subjected to fusion biopsy (39 and 32%, respectively, for the PCa and Cs PCa detection rate), while an in-bore biopsy was performed on the other 106 patients (37 and 29%, respectively, for the PCa and Cs PCa detection rate). This is in agreement with the study performed by Vanderink et al according to which there is no significant difference in the detection rate between the two biopsy techniques [24].…”
Section: Methods Of Mri-targeted Biopsysupporting
confidence: 93%
“…the study given relatively small numbers in the two cohorts. Conversely, Venderink et al [12] found the positive biopsy rate was significantly higher for any cancer detected by in-bore biopsy (85%; 193/227 patients) compared to fusion (67%; 34/51), and Costa et al [13] found the clinically significant prostate cancer detection rate was significantly higher for in-bore (61%; 63/103) than for fusion (47%; 141/300). The superiority of the in-bore approach in these two studies aligns with our findings.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Despite the important developments favoring MRI-targeted biopsy over systematic biopsy, few studies have directly compared in-bore and fusion MRItargeted biopsy, likely because most centers perform one or the other but not both. Further, the available studies [12,13], including one randomized controlled trial [14], comparing the precision of in-bore and fusion biopsies are conflicting.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The significant CDR of the target biopsy in the group I is not inferior to those in previously reported papers using MRI-TRUS fusion or in-bore MRI-guided biopsy. They have showed that their CDRs ranged from 62% to 85% in PI-RADS 5 [8,10,15,16]. However, PI-RADS 1 or 2 does not have significant cancer 100% even though this category is very unlikely or unlikely to have it [1][2][3].…”
Section: Discussionmentioning
confidence: 99%